Is BVA stifling free‐reigning ethical debate?. (21st July 2018) - Roger, Paul; Fishwick, John
Abstract : Paul Roger argues that the structure for debating and endorsing new policy decisions at BVA is not fit for purpose, and that this should be reviewed and adapted so that it can meet today's demands.